(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The emergence of the COVID19 pandemic has changed the way the world and business function, where the physical environment is shifting to a remote (online) environment. The fact emphasizes the importance of information technology (ICT) and its tools. The demand for ICT derivatives leads to the dispersion of the necessary competences for their use. The importance of this paper is reflected in the fact that the authors determine the level of women entrepreneurs’ knowledge (based on two Digital Competences framework areas) and identify which competences should be improved to be in line with market requirements. The research was conducted on a sample of 114 women entrepreneurs from February-March 2021. Based on the analysis, the authors identified the enormous gap in the second area of "Communication and Collaboration", which concerns the interaction with third parties through digital technologies.